Penerapan Head Up terhadap Kesadaran Pasien Cedera Kepala di IGD RSUD Sayang Rakyat - Nur Ummi Hayati; Akbar Asfar; Wan Sulastri Emin; Sudarman Sudarman (Rumah Sakit Ibnu Sina, Makassar, 2025)
Head injury is a traumatic disturbance of brain function that may or may not be accompanied by interstitial bleeding within the brain substance (2,4,5). Emergency management aims to prevent secondary brain injury, including optimizing ventilation/oxygenation and cerebral perfusion, as well as patient positioning. A common non-invasive measure is 30° head elevation (Head-Up) to facilitate cerebral venous drainage. To describe changes in consciousness level (Glasgow Coma Scale/GCS) following the application of a 30° Head-Up position in a patient with moderate head injury in the emergency department. A single-patient case report in the emergency department of RSUD Sayang Rakyat Makassar. The primary Outcome was serial GCS recorded at baseline before elevation (T0) and during observation until transfer. Head-Up 30° was an independent nursing intervention; oxygen therapy was recorded as collaborative therapy. A 50-year-old male (Mr. R) with moderate head injury and subdural hemorrhage. At T0 (10:15 WITA) GCS was 3-3-5; at 10:45 WITA it remained 3-3-5; it increased to 3-3-6 at 12:50 WITA and remained 3-3-6 until 13:54 WITA when the patient was transferred to the operating room. Available observation lasted approximately 3 hours 39 minutes; the planned 8-hour follow-up was not completed due to definitive transfer. In this case, 30° head elevation (with collaborative oxygen therapy) was followed by an improvement in GCS from 3-3-5 to 3-3-6 during ED observation. As descriptive evidence, this report cannot establish causality but supports the use of 30° Head-Up as part of non-invasive early management for head injury.